ANALISIS MANIFESTASI IMPLEMENTASI SCHOOL BASED MANAGEMENT PADA PENGEMBANGAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DI LEMBAGA PENDIDIKAN - Izzah, Ismatul (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to develop an interpretive framework for the Strengthening of the Pancasila Student Profile Project or abbreviated as P5in educational institutions which is synthesized from School-Based Management and reality in educational institutions. This research uses the library research research method which comes from books, journals, research results and other sources. The approach used is a qualitative approach with an interpretive paradigm. The results of this research found that there are several points of manifestation of School Based Management (SBM) or what is known as School Based Management (MBS) in the Project for Strengthening the Pancasila Student Profile, including 1). In practice, there is an urgency for educational management, where the success of an educational institution is supported by the management of the educational institution itself. 2), There are components in School Based Management such as curriculum management, educator management, student management and culture & school environment management which are interrelated in the realization of P5PPRA. 3), the role of the community and students' parents as school partners. School-Based Management is a policy program formulated by the government to officially integrate the community into the management of schools in their environment with the aim of improving their performance